Chemodynamics of metal-poor wide binaries in the Galactic halo: Association with the Sequoia event - Lim, Dongwook; Koch-Hansen, Andreas; Hansen, Camilla Juul; Lépine, Sebastien; Marshall, Jennifer L.; Wilkinson, Mark I.; Peñarrubia, Jorge (Astronomy and astrophysics, 2021)
Recently, an increasing number of wide binaries has been discovered. Their chemical and dynamical properties are studied through extensive surveys and pointed observations. However, the formation of these wide binaries is far from clear, although several scenarios have been suggested. In order to investigate the chemical compositions of these systems, we analysed high-resolution spectroscopy of three wide binary pairs belonging to the Galactic halo. In total, another three candidates from our original sample of 11 candidates observed at various resolutions with various instruments were refuted as co-moving pairs because their radial velocities are significantly different. Within our sample of wide binaries, we found homogeneity amongst the pair components in dynamical properties (proper motion and line-of-sight velocities) and also in chemical composition. Their metallicities are −1.16, −1.42, and −0.79 dex in [Fe/H] for each wide binary pair, which places these stars on the metal-poor side of wide binaries reported in the literature. In particular, the most metal-poor pair in our sample (WB2 ≡ HD 134439/HD 134440) shows a lower [α/Fe] abundance ratio than Milky Way field stars, which is a clear signature of an accreted object. We also confirmed that this wide binary shares remarkably similar orbital properties with stars and globular clusters associated with the Sequoia event. Thus, it appears that the WB2 pair was formed in a dwarf galaxy environment and subsequently dissolved into the Milky Way halo. Although the other two wide binaries appear to arise from a different formation mechanism, our results provide a novel opportunity for understanding the formation of wide binaries and the assembly process of the Milky Way.